Bauran Pemasaran dan Kepuasan Pelanggan Terhadap Loyalitas Pelanggan Ebsco Center Depok - Julianti, Julianti; Rindu, Rindu; Hafidz, Hafizurrachman (Jurnal Ilmiah Kebidanan Indonesia, 2022)
The impact of dissatisfied and disloyal customers was that many customers switch to other manufacturers so that it disrupted the sustainability of the Ebsco Center's operations and could even go out of business. The purpose of the study was to determine the direct and indirect effects and the magnitude of the 4P marketing mix and customer satisfaction on customer loyalty. This type of research was quantitative with a cross sectional design. This research was conducted in January – March 2021. The research instrument used a questionnaire. The research sample was Ebsco Center Depok customers, totaling 100 respondents. The results obtained that promotion has a direct effect on customer loyalty by 17.04%, price has a direct effect on customer loyalty by 19.11%, place has a direct effect on customer loyalty by 14.08%, product has a direct effect on customer loyalty by 15.48%, and customer satisfaction has a direct effect on customer loyalty by 16.20%. It was expected that the management of the Ebsco Center Depok to improve the marketing mix so that customers are always in close contact with the products or services of the Ebsco Center Depok, such as opening relationships to share personal experiences, making digital communications by alerting customers to schedule visits, providing information related to the service schedule, building communication good relations with customers in accordance with the wishes and needs of customers such as online registration which has not been implemented in the homecare so far.